Predicting the fire-induced structural performance of steel tube columns filled with SFRC-enhanced concrete: using artificial neural networks approach - George, Christo; Zumba, Edwin; Procel Silva, Maria Alexandra; Selvan, S. Senthil; Christo, Mary Subaja; Kumar, Rakesh; Kumar Singh, Atul; S., Sathvik; Onyelowe, Kennedy (Frontiers in Built Environment, 2024)
Predicting the axial Shortening strength of concrete-filled steel tubular (CFST) columns is an important problem that this study attempts to solve for civil engineering projects. We suggest using a deep learning-based artificial neural network (ANN) model to address this issue, taking into account the intricate relationship between steel tube and core concrete. The model, called ANN-SFRC (Steel Fiber Reinforced Concrete), surpasses an R 2 threshold of 0.90 and achieves impressive R 2 values across different types of CFST columns. Compared to traditional linear regression methods, the ANN-SFRC model significantly improves accuracy, with an observed inaccuracy of less than 3% compared to actual values. With its reliable approach to forecasting the behavior of CFST columns under axial compression, this high-performance instrument enhances safety and accuracy during the design and planning stages of civil engineering.